2017
DOI: 10.1371/journal.pone.0183311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recruitment manoeuvre on perioperative pulmonary complications in patients undergoing robotic assisted radical prostatectomy: A randomised single-blinded trial

Abstract: Robotic-assisted laparoscopic radical prostatectomy (RARP) needs a steep Trendelenburg position and a relatively high CO2 insufflation pressure, and patients undergoing RARP are usually elderly. These factors make intraoperative ventilatory care difficult and increase the risk of perioperative pulmonary complications. The aim was to determine the efficacy of recruitment manoeuvre (RM) on perioperative pulmonary complications in elderly patients undergoing RARP. A total of 60 elderly patients scheduled for elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 36 publications
2
34
1
4
Order By: Relevance
“…Seven RCTs including a pooled total of 1609 participants investigated the effect of lung protective intraoperative ventilation strategies on PPCs 47484950515253. The definition of lung protective ventilation varied between trials, but for the purposes of analysis we used a single definition of reduced tidal volumes (≤8 mL/kg) and at least 5 cm H 2 O positive end expiratory pressure together with intermittent recruitment manoeuvres.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven RCTs including a pooled total of 1609 participants investigated the effect of lung protective intraoperative ventilation strategies on PPCs 47484950515253. The definition of lung protective ventilation varied between trials, but for the purposes of analysis we used a single definition of reduced tidal volumes (≤8 mL/kg) and at least 5 cm H 2 O positive end expiratory pressure together with intermittent recruitment manoeuvres.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 18 RCTs investigating different aspects of intraoperative ventilation were identified in this review,474849505152535455565758596061626364 including a pool of 2171 patients. Seven studies were of patients having open abdominal surgery,47495051545664 five were of exclusively minimally invasive surgery (laparoscopic or robotic),5255585960 three were of lung cancer resection surgery (open or thoracoscopic),485761 one was of neurosurgery,62 one was obstetric,53 and one recruited patients from a range of specialties united in having prolonged surgery 63…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the use of zero PEEP or PEEP alone, recruitment maneuvers have been shown to increase end expiratory lung volume, improve compliance, and reduce chest wall elastance during laparoscopic surgery 67686970. Investigators have shown that recruitment maneuvers lead to improved intraoperative oxygenation in abdominal surgery, thoracic surgery with OLV, post-cardiopulmonary bypass, and procedures requiring Trendelenberg positioning 71727374757677. These benefits are unfortunately short lived, as atelectasis is thought to recur within 40 minutes 78…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%
“…These include raised airway pressure with atelectasis, cerebral and facial oedema, raised intra-ocular pressure, and traction on lower limbs with neuropraxia. 10,11 No documented cases of these complications were noted in this cohort of patients.…”
Section: Surgical Techniquementioning
confidence: 71%